2012
DOI: 10.1111/j.1538-7836.2012.04798.x
|View full text |Cite
|
Sign up to set email alerts
|

Markers of coagulation, fibrinolysis and inflammation in relation to post‐thrombotic syndrome

Abstract: Summary. Background: Post-thrombotic syndrome (PTS) occurs in 20-50% of patients after a deep venous thrombosis (DVT). It is difficult to accurately predict which patients will develop PTS. Biomarkers could be a valuable tool for PTS risk assessment. Objectives: To investigate whether increased levels of factor (F)VIII, C-reactive protein (CRP) or D-dimer, over time, are associated with the development of PTS in patients after an acute DVT. Methods: PTS status was assessed using the Villalta scale. Blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 43 publications
8
76
1
2
Order By: Relevance
“…However, all are consistent in showing ipsilateral recurrence to be predictive of future PTS (Table 6). 7,8,47,51,73,75 Residual thrombosis after treatment of DVT has also been shown to be a predictor of PTS. 27,28,62,76 In patients with a first episode of DVT, the risk of PTS was 1.6-fold higher (95% CI, 1.0-2.5) in those with residual proximal thrombosis compared with those without this finding.…”
Section: Risk Factors Apparent During Dvt Treatment and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all are consistent in showing ipsilateral recurrence to be predictive of future PTS (Table 6). 7,8,47,51,73,75 Residual thrombosis after treatment of DVT has also been shown to be a predictor of PTS. 27,28,62,76 In patients with a first episode of DVT, the risk of PTS was 1.6-fold higher (95% CI, 1.0-2.5) in those with residual proximal thrombosis compared with those without this finding.…”
Section: Risk Factors Apparent During Dvt Treatment and Follow-upmentioning
confidence: 99%
“…In a recent prospective cohort study, C-reactive protein levels >5 mg/L 12 months after the index DVT independently predicted PTS (OR, 8.0; 95% CI, 2.4-26.4). 75 In 2 studies, persistently elevated levels of D-dimer, an indirect marker of coagulation activation, were predictive of PTS when measured at various intervals after DVT, 10,78 especially when measured when the patient was off anticoagulant treatment. It is not yet known whether the aforementioned biomarkers may have clinical utility to identify patients with acute DVT who are at risk for PTS.…”
Section: Role Of Biomarkers To Predict Ptsmentioning
confidence: 99%
“…MPV admission mean platelet volume levels, PDW admission platelet distribution width levels, MPV6 mean platelet volume levels at 6 month follow-up, PDW6 platelet distribution width levels at 6 month follow-up, D%MPV percent change for mean platelet volume levels, D%PDW percent change for platelet distribution width levels a Patients with residual venous thrombosis b Patients with complete resolution of thrombus There are limited studies investigating biomarkers in RVT after DVT. Biomarkers associated with coagulation and inflammation may play a role in the resolution of thrombosis [26,27]. Cosmi et al [28] demonstrated that repeated D-dimer testing after cessation of anticoagulant therapy for the first episode of unprovoked VTE could help determine the duration of the treatment.…”
Section: Discussıonmentioning
confidence: 99%
“…A number of studies have shown that PTS is closely associated with systemic inflammation and subsequent tissue remodeling and fibrosis [5,16]. Given reports on unfavorable clot properties in inflammatory states [10,11], we hypothesized that a prothrombotic clot phenotype is associated with a future risk of PTS.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent ipsilateral DVT is the strongest risk factor for PTS [1,4,5]. Older age, obesity and proximal DVT have also been shown to increase the risk of PTS in several studies [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%